REVISIÓN TAXONÓMICA DEL GÉNERO SOLERVICENSIA BARR, 1979 (COLEOPTERA: CLERIDAE: KORYNETINAE) (Acta Entomológica Chilena, 2022)
A taxonomic revisión of the species ascribed to Solervicensia Barr, 1979, is made. Only two species arerecognized: Solervicensia ovatus (Spinola, 1849) and S. basipennis (Pie, 1950). The following taxa are establishedas new synonyms of S. ovatus: Korynetes aeneus Philippi y Philippi, 1864, Lebasiella limbipennisChevrolat, 1876, Lebasiella lineata Pie, 1950, Lebasiella rufwollis Pie, 1950, Lebasiella ruficollis var. sinuatelineataPie, 1950, Lebasiella Duboulayi Pie, 1950 and the varieties of Lebasiella subanchoralis Chevrolat,1976 (species previously synonymyzed with 5. ovatus by Schenkling, 1916): L. s. subinterrupta Pie,1950, L.s. ininterrupta Pie, 1950, Ls. latemetallica Pie 1950, and L.s. apicalis Pie, 1950. A redescription ofS. ovatus is provided.